Membangun Kesadaran dan Kesiapsiagaan Bencana Tsunami pada Siswa SMKN 10 Konawe Selatan - Amritzal Nur Firdaus; Ali Okto; Hasria Hasria; Bahdad Bahdad; Asri Arifin; Isman Saleh; Rio Irhan Mais Cendra Jaya (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2026)
Indonesia is highly vulnerable to tsunami disasters due to its location at the convergence of three major active tectonic plates. One of the most effective strategies for disaster risk reduction is improving public awareness and preparedness from an early age through school-based education. This community service program aimed to enhance tsunami disaster awareness and preparedness among students of SMKN 10 Konawe Selatan. The program was conducted through three stages: preparation, implementation, and evaluation. Educational activities were delivered through lectures, video presentations, interactive discussions, and tsunami disaster response simulations. The effectiveness of the program was evaluated using pre-test and post-test instruments to measure students’ knowledge improvement. The results showed a significant increase in students’ understanding of tsunami concepts, causes, early warning signs, self-rescue procedures, and evacuation measures. The disaster response simulation provided students with practical experience in implementing proper evacuation procedures. In addition, students demonstrated high enthusiasm and active participation throughout the program. The findings indicate that disaster education combined with simulation-based learning is an effective approach to improving tsunami awareness and preparedness among students. Continuous implementation of similar programs is recommended to strengthen disaster preparedness culture and reduce future disaster risks and impacts.